Interpretation and Performance Practice on Humoreske by Robert Schumann - Meesap, Yanisa; Chulapan, Panjai (Rangsit Music Journal, 2024)
This research article is about the interpretation and performance practice of Humoreske, Op.20 by Robert Schumann (1810-1856), a German composer and music critic. The purpose of this article is to study Schumann’s biography, history of Humoreske, Op.20 and to enhance the ability to interpret and perform with proper techniques. There are 6 sections in this piece. It is a piece that not only highlights Schumann’s diverse personalities, but also show his unique style and creativity as a composer. There are melodies that evokes both joy and sadness, employs a mix of fast and slow tempos, complexed harmonies and advanced instrumental techniques which make it special and unique characteristic in music of Romantic era. It is considered a challenging piece according to interpretation and performing techniques. Pianists must study the composition thoroughly and convey the piece with perfection.